An undiagnosed patient with skin rash, polyarthritis, and edema responding to low-dose colchicine: A case report. (June 2021) - Maita, Hiroki; Kobayashi, Tadashi; Akimoto, Takashi; Osawa, Hiroshi; Hasui, Keisuke; Kato, Hiroyuki
A 54-year-old man was referred to our hospital with painful rashes on the extremities. He also developed polyarthritis and pitting pedal edema. Blood tests showed no specific autoantibodies and were negative for human leukocyte antigens B51, B15, and B27. Lower extremity venous ultrasonography and computed tomography angiography showed no vascular disorders. Skin biopsy showed no evidence of thrombosis or vasculitis. Direct fluorescence antibody analysis showed no antibody or complement deposition. Joint ultrasonography showed mild synovial thickening and/or synovial effusion in the extremities. Non-steroidal anti-inflammatory drugs and topical steroids were administered, followed by oral steroids. However, the signs and symptoms did not improve. Oral steroids were discontinued, and colchicine (0.5 mg/day) was administered. Thereafter, the symptoms of arthritis improved, and no skin rash developed. In potentially inflammatory conditions with skin rash, edema, and polyarthritis that are difficult to diagnose, low-dose colchicine administration may be considered for prompt relief of symptoms.